Seed-borne fungi of chilli - Ho, Yin Wan; Kanapathipillai, V.; Hashim, M. (1990)
Untreated chilli (Capsicum annum, Kulai) seeds obtained from the Federal Experimental Station, Serdang, Selangor, were screened for seed-borne fungi. Seeds treated with 10% chlorox, fungicides Thiram and Captan and hot water (55°C, 60°C and 70°C) for 10 min were also screened. For each treatment, 400 seeds were screened using the agar medium and blotter methods. Fungi isolated were tested for pathogenicity on chilli seeds and seedlings. Twenty-one species from 14 genera of fungi viz, Aspergillus, Cephalosporium, Clardoporium, Curvularia, Fusarium, Geotrichum, Gliocladium, Nodulisporium, Paecilomyces, Penicillium, Rhizoctonia, Rhizopus, Trichoderma and Schizophyllum were isolated from the untreated seeds. Treatments of seeds with Captan and Thiram completely eradicated all the fungal species, except Aspergillus niger and A. flavus ) from the seeds without affecting their germination. On the other hand, treatment of seeds with 10% chlorox was found to be less effective. Hot water treatments of seeds at 55°C and 60°C were found to be effective in killing most of the seed-borne fungi while still maintaining a high percentage of seed germination. Hot water treatment at 70°C eradicated all fungi except A. niger and A. flavus but this treatment is not recommended as it killed all the seeds. Preliminary pathogenicity test with all the fungal isolates on the chilli seeds indicated that 8 fungal species (Aspergillus niger, A. flavus, Rhizopus sp. Cephalosporium. sp. Penicillium citrinum. Fusarium oxysporum, F. semitectum and Curvularia lunata) were pathogenic. Further pathogenicity test, with the 8 fungal species on 100 seeds each, showed that all the 8 species were pathogenic, causing infection and death of the seeds, thus resulting in significant (P-0.05) reduction in germination (Table 1). Mazanah (1977) has also shown A. niger, A. flavus, Fusarium sp, Curvularia sp and Rhizopus sp to be pathogenic to chilli seeds. Pathogenicity test with all fungal isolates on chilli seedlings (75 seedlings for each isolate) showed that 9 fungal species were pathogenic to the seedlings (Table 2).